(untitled) (Orfeu, 2020)
To understand the music history writing about the state of Santa Catarina, a mapping of the academic researches defended on this theme is carried out in Brazilian’s graduate programs databases. The works are problematized from specific approaches, such as the institutional, biographical perspective and focused on the description of musical genres and movements in Santa Catarina. Mapped academic researches contributes to overcoming a partial and pretentious musical literature. In historical, musicological or ethnographic research there is a predominance of works focused on music in the state capital, with a gradual process of decentralization. Finally, all the mapped works bring important contributions to the writing and understanding of past and present Santa Catarina’s musical culture.